Transcriptomic analysis of Blumea laciniata responses to PEG-simulated drought stress - Wang, Hongjuan; Dai, Yongdong; Zhang, Mingyuan; Chen, Yang (Frontiers in Plant Science, 2025)
IntroductionBlumea laciniata (B. laciniata), a well-documented ethnomedicinal species in Chinese pharmacopeia, has demonstrated significant therapeutic efficacy against various infectious diseases. With the growing number of studies, medicinal plants are being acknowledged as valuable natural resources for combating stress. Elucidating the drought tolerance mechanisms of such species is crucial for formulating adaptive cultivation strategies to mitigate climate change-induced agricultural challenges.MethodsIn this study, drought stress was induced using two polyethylene glycol (PEG) concentrations (20% and 30%). Furthermore, RNA-seq and WGCNA (Weighted gene co-expression network analysis) were conducted on B. laciniata plants at five time points (0, 1, 2, 4, and 7 days) pre- and post-stress exposure.ResultsB. laciniata demonstrates natural drought tolerance, as observed in field studies. PEG-induced drought stress at two concentrations (20% and 30%) impaired leaf development, resulting in chlorosis, curling, wilting, and necrosis, with 30% PEG showing greater damage. Moreover, pro and SOD levels increased with stress duration. RNA-seq analysis demonstrated distinct transcriptional reprogramming in B. laciniata leaves under PEG stress. Venn and KEGG enrichment analyses revealed that the plant primarily responds to drought stress by regulating phenylpropanoid and flavonoid biosynthesis pathways. Furthermore, WGCNA analysis identified two transcription factors (TFs), GRF2 and NF-YA3, as key regulators associated with the drought resistance of B. laciniata.DiscussionOur study provides a theoretical basis for elucidating the molecular mechanisms underlying drought resistance in B. laciniata plants and provides new genetic resources for the study of drought resistance in this crop.